1989
DOI: 10.1007/bf01658403
|View full text |Cite
|
Sign up to set email alerts
|

Results of treatment of patients with hepatocellular carcinoma with severe cirrhosis of the liver

Abstract: We retrospectively classified patients with hepatocellular carcinoma by the results of tests of 15-minute indocyanine green retention (ICGR15). Of the 201 patients with hepatocellular carcinoma admitted to our department in the past 6 years, 36 patients were assigned to group 1 (ICGR15 less than 10.0%), 81 patients to group 2 (ICGR15 = 10.1-20.0%), and 84 patients to group 3 (ICGR15 greater than or equal to 20.1%). Of the total 201 patients, 72% underwent liver resection (78% of group 1 patients, 80% of group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 11 publications
0
19
0
Order By: Relevance
“…The main purposes of preoperative TACE for resectable HCC are: (1) to improve the detection rate of the other lesions not apparent on pre-TACE radiologic study; (2) to convert initially unresectable tumors to resectable ones, i.e., to induce regression of a huge tumor, enabling safer resection, and (3) to improve long-term results of surgery [11,12,13,14,15]. However, the efficacy of preoperative TACE for resectable HCC is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main purposes of preoperative TACE for resectable HCC are: (1) to improve the detection rate of the other lesions not apparent on pre-TACE radiologic study; (2) to convert initially unresectable tumors to resectable ones, i.e., to induce regression of a huge tumor, enabling safer resection, and (3) to improve long-term results of surgery [11,12,13,14,15]. However, the efficacy of preoperative TACE for resectable HCC is still controversial.…”
Section: Discussionmentioning
confidence: 99%
“…TACE was initially used as a palliative therapeutic procedure for unresectable HCC [9, 10] and now, it is frequently performed as a preoperative adjuvant therapy for resectable HCC in some medical centers [11,12,13,14,15]. According to previous studies, however, preoperative TACE has both possible advantages and disadvantages [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In patients who underwent PVE, the left liver (nonembolized) volume increased after PVE and liver resection; however, when comparing the volume of the left liver at the beginning of treatment and 4 weeks after surgery, the extent of the volume increase in the left liver in patients who underwent PVE was similar to that in those who did not undergo PVE. This indicated that PVE causes regeneration of the left liver in two stages [6,7].…”
Section: Portal Vein Embolization Before Major Hepatectomymentioning
confidence: 90%
“…Unlike the normal liver, which, within [3][4][5][6][7][8][9][10][11][12] months can regenerate to its original size and function, even after 80% resection, the cirrhotic liver has impaired regenerative ability. Indeed, until recently, the cirrhotic liver was thought to be unable to regenerate [7].…”
Section: Impaired Regenerationmentioning
confidence: 99%
“…In the last 20 [4,5]. Conversely, 10-20% of patients with cirrhosis from any etiology, will go on to develop HCC [3,6].…”
Section: Introductionmentioning
confidence: 99%